BEYOND REPRESENTATION: FEMINIST COMMUNICATION AND THE DISCURSIVE CONSTRUCTION OF MUSLIM WOMEN’S LEADERSHIP IN AISYIYAH’S DIGITAL HAGIOGRAPHY - Sumadi (Universitas Muhammadiyah Metro, 2026)
Abstract This study explores how Muslim women’s leadership is discursively constructed in Aisyiyah’s digital hagiography through the lens of feminist communication. Moving beyond representational analysis, the study conceptualizes leadership as a communicative and ideological process shaped by narrative, discourse, and symbolic practices in digital religious contexts. Drawing on qualitative analysis of Aisyiyah’s online biographical narratives, the findings reveal that leadership is constructed through interrelated dimensions: pedagogical authority, moral exemplarity, communicative competence, organizational modernity, gender negotiation, collective practice, and reformist agency. These discursive formations produce a hybrid model of leadership that simultaneously expands women’s public roles while remaining anchored in Islamic ethical frameworks. The study argues that digital hagiography functions as a normative communicative infrastructure that legitimizes and reproduces gendered authority. By integrating feminist communication and discourse analysis, this article contributes to understanding how Muslim women’s leadership is negotiated, institutionalized, and transformed in contemporary digital Islamic publics.